Transformational Leadership in Overcoming Teacher Burnout - Vani Sasmiaji; Sukirman Sukirman; Suyatno Suyatno (Eduvest - Journal of Universal Studies, 2025)
This study discusses transformational leadership in overcoming private school teacher burnout. This study focuses on the application of transformational leadership style carried out by the principal to overcome burnout. Teacher burnout should be addressed immediately so as not to worsen the impacts caused. The purpose of this study is to describe the transformational leadership style applied in Bumitama private schools in overcoming teacher burnout. This study was conducted at Bumitama private schools located in West Kotawaringin Regency. This research method uses a qualitative approach with a case study research design. Primary data sources were obtained from interviews with the principal and secondary data sources were obtained from relevant observations and documentation. Data analysis techniques used include data collection, data reduction, data presentation, and drawing conclusions and verification. The results of the study indicate that Bumitama private schools take various actions such as providing opportunities for teachers to improve their competence, being open to new ideas or ideas and creating equality in work relationships. This is a form of transformational leadership style in overcoming and reducing the level of teacher burnout.